MODERN TECHNOLOGIES IN ENGLISH LANGUAGE LEARNING: FROM VIRTUAL REALITY TO ARTIFICIAL INTELLIGENCE - Волкова , Елена (Scientific practical conference, 2025)
The article deals with the transformative impact of contemporary educational technologies on English language acquisition. It analyzes the implementation of artificial intelligence, virtual and augmented reality, gamification, big data analytics and neurotechnology in creating personalized and effective learning experiences. The study highlights how these innovations enhance speaking practice, vocabulary acquisition, and grammatical accuracy while addressing ethical considerations and the importance of maintaining human interaction in the learning process.